2016
DOI: 10.1021/acs.energyfuels.6b01868
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Thermal and Catalytic Cracking of Waste Motor Oil to Diesel-like Fuels

Abstract: Considering the serious impact caused to the environment by the inappropriate disposal of waste motor oils, it is essential to find alternative mechanisms to handle and dispose these wastes in a controlled process. The reuse of waste motor oil as a resource for the synthesis of diesel-like fuels provides an alternative way for the disposal of this residue in a feasible, sustainable, and environmentally responsible way. This work addresses the kinetic study of the catalytic cracking of waste motor oil using mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The ever-increasing consumption of petroleum/synthetic oil products (such as lubricating oil, transformer oil, and so forth) have led to the generation of million tons of wasted oil every year (wasted oil refers to an oil that has lost its function due to the inclusion of impurities and the change in composition) . The management and disposal of them have therefore become a critical issue for governments due to the relevant environmental concerns, such as the oil-induced water and soil pollution . Oil regeneration via a stepwise purification and refining strategy is one promising solution, which can also contribute to saving petroleum resources. , The purification process is intended to remove undesired impurities in oil, including water, particles, polymers, and ions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ever-increasing consumption of petroleum/synthetic oil products (such as lubricating oil, transformer oil, and so forth) have led to the generation of million tons of wasted oil every year (wasted oil refers to an oil that has lost its function due to the inclusion of impurities and the change in composition) . The management and disposal of them have therefore become a critical issue for governments due to the relevant environmental concerns, such as the oil-induced water and soil pollution . Oil regeneration via a stepwise purification and refining strategy is one promising solution, which can also contribute to saving petroleum resources. , The purification process is intended to remove undesired impurities in oil, including water, particles, polymers, and ions .…”
Section: Introductionmentioning
confidence: 99%
“…1 The management and disposal of them have therefore become a critical issue for governments due to the relevant environmental concerns, such as the oil-induced water and soil pollution. 2 Oil regeneration via a stepwise purification and refining strategy is one promising solution, which can also contribute to saving petroleum resources. 3,4 The purification process is intended to remove undesired impurities in oil, including water, particles, polymers, and ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The equipment used for the thermal cracking of plastics was a Precision Scientific Petroleum Herzog distiller with a maximum power of 1100W. A detail description of the setup can be found at Vargas et al [24]. For each experiment, 40 g of plastic pellets (i.e.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Pyrolysis is a good option for converting wastes into fuels/chemicals via thermal treatment. Various types of solid and liquid wastes, including polyethylene (PE), polypropylene (PP), polystyrene (PS), tires, sludge, and motor oil wastes, have been recycled after treatment with a pyrolysis process. In addition to pyrolysis of waste materials, pyrolysis of lignocellulosic biomass and its main components, cellulose and lignin, has also been widely investigated by the scientific community. At present, lignocellulosic biomass is the only renewable source of liquid fuel . Over the last three decades, co-pyrolysis of lignocellulosic biomass with polymers has become one of the most popular areas of scientific research. The advantages of co-pyrolysis include , the improvement of pyrolysis oils, improvement in organic matter of solid products, and no requirement for special instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2017, motor oil was consumed at approximately 243.000 t in Turkey . Obviously, recycling of waste motor oil is crucial, and recent studies have demonstrated that diesel-like fuels can be produced from various waste engine oils. , …”
Section: Introductionmentioning
confidence: 99%